Fabrication and Validation of Sub-Cellular Carbon Fiber Electrodes - Julianna Richie; Joseph G. Letner; Autumn Mclane-Svoboda; Yu Huan; Dorsa Haji Ghaffari; Elena Della Valle; Paras R. Patel; Hillel J. Chiel; Galit Pelled; James D. Weiland; Cynthia A. Chestek (IEEE, 2024)
Multielectrode arrays for interfacing with neurons are of great interest for a wide range of medical applications. However, current electrodes cause damage over time. Ultra small carbon fibers help to address issues but controlling the electrode site geometry is difficult. Here we propose a methodology to create small, pointed fiber electrodes (SPFe). We compare the SPFe to previously made blowtorched fibers in characterization. The SPFe result in small site sizes $(105.4 ± 20.8~μ \text{m}^{{2}})$ with consistently sharp points (20.8 ± 7.64°). Additionally, these electrodes were able to record and/or stimulate neurons multiple animal models including rat cortex, mouse retina, Aplysia ganglia and octopus axial cord. In rat cortex, these electrodes recorded significantly higher peak amplitudes than the traditional blowtorched fibers. These SPFe may be applicable to a wide range of applications requiring a highly specific interface with individual neurons.